Evidence for negative selection of gene variants that increase dependence on dietary choline in a Gambian cohort. Issue 8 (28th April 2015) - Silver, Matt J.; Corbin, Karen D.; Hellenthal, Garrett; Costa, Kerry‐Ann da; Dominguez‐Salas, Paula; Moore, Sophie E.; Owen, Jennifer; Prentice, Andrew M.; Hennig, Branwen J.; Zeisel, Steven H.
Abstract : Choline is an essential nutrient, and the amount needed in the diet is modulated by several factors. Given geographical differences in dietary choline intake and disparate frequencies of single‐nucleotide polymorphisms (SNPs) in choline metabolism genes between ethnic groups, we tested the hypothesis that 3 SNPs that increase dependence on dietary choline would be under negative selection pressure in settings where choline intake is low: choline dehydrogenase (CHDH) rs12676, methylenetetrahydrofolate reductase 1 (MTHFD1) rs2236225, and phosphatidylethanolamine‐N‐methyltransferase (PEMT) rs12325817. Evidence of negative selection was assessed in 2 populations: one in The Gambia, West Africa, where there is historic evidence of a choline‐poor diet, and the other in the United States, with a comparatively choline‐rich diet. We used 2 independent methods, and confirmation of our hypothesis was sought via a comparison with SNP data from the Maasai, an East African population with a genetic background similar to that of Gambians but with a traditional diet that is higher in choline. Our results show that frequencies of SNPs known to increase dependence on dietary choline are significantly reduced in the low‐choline setting of The Gambia. Our findings suggest that adequate intake levels of choline may have to be reevaluated in different ethnic groups and highlight a possible approach for identifying novel functional SNPs under the influence of dietary selective pressure.—Silver, M. J., Corbin, K. D., Hellenthal, G., da Costa, K.‐A., Dominguez‐Salas, P., Moore, S. E., Owen, J., Prentice, A. M., Hennig, B. J., Zeisel, S. H. Evidence for negative selection of gene variants that increase dependence on dietary choline in a Gambian cohort. FASEB J. 29, 3426‐3435 (2015). www.fasebj.org